Contagion, bank lending spreads, and output fluctuations - Agénor, Pierre-Richard, 1957- 1957- (Policy research working paper, 1999)
A positive historical shock to external spreads can lead to an increase in domestic spreads and a reduction in the cyclical component of output. Shocks to external spreads immediately after the Mexican peso crisis had a sizable effect on movements in output and domestic interest rate spreads in Argentina